Covid-19, nutrition and pseudoscientific claims - Abdolreza Norouzy (Indonesian Nutrition Association, 2022)
The COVID‐19 infodemic is full of false claims, half backed conspiracy theories and pseudoscientific therapies, regarding the diagnosis, treatment, prevention, origin and spread of the virus. Correcting misrepresentations should be viewed as a professional responsibility